Asymmetries in the application of Unmanned Aerial Vehicles in different phases of Disaster Risk Management (DRM) - Leandro Ludwig; Marcos Antônio Mattedi; Eduardo Augusto Werneck Ribeiro; Maiko Rafael Spiess (Desenvolvimento e Meio Ambiente, 2023)
This article aims to highlight the knowledge gaps identified in the use of Unmanned Aerial Vehicles in the different phases of Disaster Risk Management (DRM). To this end, a bibliographic review of 254 articles reporting on UAVs and natural disasters in the period 2000-2020 is presented. To select a sample of publications that address the relationship between drones and natural disasters, from 2000 to 2020, quantitative searches were made on the Google Scholar. Only the articles published in journals or events were considered for this purpose. The searches were carried out using the following terms: disasters; hazards; risk; natural disasters; UAV; drone. The linguistic variation of the terms was also considered (terms in English, Spanish and Portuguese). As a main finding, it is argued that there are few studies on the use of UAVs in risk mitigation in the pre-disaster phase. To develop this argument, the article begins with a discussion of the structure of DRM, then addresses the use of drones in natural disasters, and finally develops a critique of the asymmetry that exists in the use of UAVs in DRM.